Doppler Illusion Prevails Over Pratt Effect in Risset Tones. (December 2018) - Villegas, Julián; Fukasawa, Naoki
Changes in frequency such as those found in Risset tones have been associated with moving sound sources in the vertical plane (Pratt effect) and the horizontal plane (Doppler illusion). We investigated the reported origin and motion of unspatialized Risset tones presented monotically and diotically, and Risset tones simulated to be in the sagittal or coronal plane, approaching or receding, from above or horizontally. Independent of the artificial spatialization used (none, spatializing frequency components collectively or individually, elevated or not), upward glissandi were more likely to be judged as approaching than receding, and downward glissandi as receding than approaching, in most cases from the horizon. Glissandi associations with horizontal movements were more common in stimuli simulated on the sagittal plane than in stimuli simulated on the coronal plane. These findings suggest that the Doppler illusion is stronger than the Pratt effect, at least for Risset tones presented over headphones and simulated to be in the sagittal plane. These findings may contribute to better understanding of the association between auditory motion perception and changes in frequency.